Regulatory T Cells and Profile of FOXP3 Isoforms Expression in Peripheral Blood of Patients with Myelodysplastic Syndromes - Galina A. Dudina; Almira D. Donetskova; Marina M. Litvina; Alexander N. Mitin; Tatiana A. Mitina; Sergey A. Polyakov (Advances in Hematology)
We have investigated the frequencies of regulatory T cells and the level of FOXP3 isoforms expression in peripheral blood of patients with myelodysplastic syndromes and found the significant reduction of regulatory T cells at all stages of the disease. At the same time in untreated patients, we observed the shift in the FOXP3 isoforms expression profile towards the full-length molecule possibly due to inflammation. Based on the already known information about the potentially higher functional activity of FOXP3 molecule lacking exon 2, we have also hypothesized that our finding may explain the high risk of autoimmune disorders in this disease.